1998
DOI: 10.2214/ajr.171.1.9648764
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of needle size for breast biopsy: comparison of 14-, 16-, and 18-gauge biopsy needles.

Abstract: OBJECTIVE. Thepurpose ofourstudy wastocompare thequantity andquality oftissueharvested from breast biopsy when using 14-, 16-, and 18-gauge â€oe¿ long-throw― needles. SUBJECTS AND METHODS.Weperformed aprospective randomized study in64patients with 66 breast lesions. Under stereotactic guidance, passes were made in random order with each of the three biopsy needles in each lesion. Samples were measured for tissue area and scored for their quality. All lesions, including benign and malignant lesions and lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 28 publications
1
36
0
5
Order By: Relevance
“…However, the results of our study for diagnosing non-palpable solid breast lesions using US 18-gauge CNB show a diagnostic accuracy comparable to that noted in studies in which 14-gauge needles were used. A suggestion supported by our findings is that lesions in which mammography reveals the presence of microcalcifications frequently consist of friable and fatty tissue (12,21,22), both of which are believed to be responsible for incorrect diagnosis with smaller needles (12,21). We found that was much higher than in earlier reports, and that sensitivity was as high as when larger needles were used.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the results of our study for diagnosing non-palpable solid breast lesions using US 18-gauge CNB show a diagnostic accuracy comparable to that noted in studies in which 14-gauge needles were used. A suggestion supported by our findings is that lesions in which mammography reveals the presence of microcalcifications frequently consist of friable and fatty tissue (12,21,22), both of which are believed to be responsible for incorrect diagnosis with smaller needles (12,21). We found that was much higher than in earlier reports, and that sensitivity was as high as when larger needles were used.…”
Section: Discussionsupporting
confidence: 81%
“…With the aim of reducing possible complications, including local hemorrhage, discomfort and tumor seeding along the needle track, an 18-gauge needle is used for US CNB. It has been reported that the risk of complications correlates with the size of needle used (9 11), and though a smaller (18-gauge) needle is in this respect advantageous, reports have claimed that for CNB diagnosis, a large needle (14-, or 16-gauge) is more accurate (12,13).…”
mentioning
confidence: 99%
“…An 18-G needle is the most common needle calibre used to obtain prostatic tissue, although this convention is derived from the transrectal approach, which requires this needle size. As reported in previous breast cancer trials, tissue harvested using smaller needles is frequently friable and tends to fragment more often than tissue harvested using larger ones [5]. The use of a larger calibre needle certainly increases the amount of tissue harvested during biopsy and could potentially improve histological sampling, thereby enhancing the accuracy of prostate cancer diagnosis.…”
Section: Introductionmentioning
confidence: 85%
“…In one study, the use of an 18-G needle provided a 6.4-mm 2 specimen, compared with the 9.6-mm 2 (mean values) sample obtained using a 16-G needle [5]. As a result, the quality of the tissue samples obtained during biopsy was significantly superior when a 16-G needle was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation